The Relationship Between Perineal Care Practices And Nutritional Status Of Postpartum Mothers And Perineal Wound Healing Time At Oekam Health Center - Yusti Anggi Umbu Pingge (Journal for Research in Public Health, 2026)
Perineal lesions are prone to infection, especially if the healing process takes a long time and the treatment is improper. The purpose of this study was to determine the relationship between the treatment and nutritional status of postpartum mothers and the healing time of perineal wounds at the Oeekam Health Center. The design of the correlation research with a cross sectional approach. The population is all postpartum mothers with perineal lesions at the Oeekam Health Center, with a total sampling technique obtained a sample of 16 respondents. The independent variables are postpartum care and nutritional status, while the dependent variables are the length of time perineal wound heals. The instrument used observation, data analysis using linear regression test (α = 0.05). The results showed that half of the respondents (50.0%) had adequate perineal treatment, most of the respondents (62.5%) had normal nutritional status and half of the respondents (50.0%) had old perineal wound healing. The results of the simultaneous analysis showed that p-value = 0.000 < α = 0.05 then H0 was rejected and H1 was accepted, which means that there is a relationship between perineal care and nutritional status with the healing time of perineal wounds. Perineal care and nutritional status are interrelated in influencing the length of wound healing. Good wound care must be followed by good nutritional status so that wound healing takes place quickly. Postpartum mothers are expected to pay more attention to perienum care efforts and increase the consumption of nutritious food during the postpartum period.